Fabrication of MoS2 Nanowire Arrays and Layered Structures via the Self‐Assembly of Block Copolymers. Issue 11 (1st March 2016) - Chaudhari, Atul; Ghoshal, Tandra; Shaw, Matthew T.; O'Connell, John; Kelly, Roisin A.; Glynn, Colm; O'Dwyer, Colm; Holmes, Justin D.; Morris, Michael A.
Abstract : The electronics industry is beginning to show interest in 2D molybdenum disulfide (2D‐MoS2 ) as a potential device material due to its low band gap and high mobility. However, current methods for its synthesis are not "fab" friendly and require harsh environments and processes. Here, a novel method to prepare MoS2 nanowire arrays and layered structures via self‐assembly of a block copolymer system is reported. Well‐controlled films of microphase separated line‐space nanopatterns have been achieved by solvent annealing process. The self‐assembled films are used as "templates" for the generation of nonstoichometric molybdenum oxide by in situ inclusion technique following UV/Ozone treatment. Well‐ordered array of MoS2 and a layered structure are then prepared by chemical vapor deposition using sulfur powder at lower temperature. The surface morphology, crystal structure, and phases are examined by different microscopic and spectroscopic techniques. This strategy can be extended to several other 2D materials systems and open the pathway toward better optoelectronic and nanoelectromechanical systems. Abstract : A simple technique is demonstrated here to fabricate 2D molybdenum disulfide (MoS2 ) nanowires with controlled orientation and density at spatially well defined locations on a substrate based on an in situ hard‐mask pattern formation approach by microphase‐separated block‐copolymer thin films. The effect of temperature change on the synthesis of MoS2 from MoO3 is investigated.